Kegiatan Penanaman Pohon di Lingkungan Kampus II Universitas Muhammadiyah Palangka Raya dalam Rangka Mengurangi Resiko Banjir: Tree Planting Activities in Campus II Universitas Muhammadiyah Palangka Raya in Order to Reduce Flood Risk - Nevy Amirda Oktavia; Avif Rifai Karuniadi; Sekar Pratiwi; Achmad Imam Santoso (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Reforestation is an effort to plant trees or plants in places considered to be able to grow and develop these plants. Greening/reforestation is done to restore a beautiful and healthy environment without pollution. The atmosphere around the housing complex for the lecturers of Campus II University of Muhammadiyah Palangka Raya, there is still some vacant land, the trees are scarce, and each resident's house also has a few plants on its terraces. The results of the survey that we received were that the people's level of awareness about the importance of plants was shallow. This is the basis for this community service activity, by carrying out reforestation to build awareness of the importance of reforestation by planting trees to reduce the risk of flooding. This community service was carried out by 26 high school / vocational / MA students throughout Palangkaraya City and 18 students of Environmental Engineering, University of Muhammadiyah Palangka Raya, as many as 2020 and 2021 students by providing plant seeds and planting them directly on each side of the road in front of residents' houses. Plant seeds used are fruits and others. The result of the implementation of this activity is that the residents feel helped and happy; they also happily accept this activity; the residents think that it is easier for us students and students who directly plant their plants in their complex to try to reduce the risk of flooding or erosion.